Molecular mechanisms underlying antiproliferative effect of tricyclohexylphosphine gold (i) mercaptobenzoate derivatives on human breast and ovarian carcinoma cell lines - Ang, Kok Pian (2017)
Breast and ovarian cancers are in the list of top three female cancers. Hormonal problem and family genetic background play important role in these two types of cancer. In cancer research, p53 deems to be the key regulator in the apoptosis events (intrinsic and extrinsic). Many studies have been focusing on the therapeutic effects of the metal complexes including gold complexes due to its potential in exhibiting various medical therapeutic benefits. Thus, a series of gold complexes has been synthesized from the precursor tricyclohexylphosphine gold (I) and mercaptobenzoic acid ligands. The Tricyclohexylphosphinegold (I) Rmercaptobenzoate derivatives are yielded at different ligand position of ortho (2), meta (3) and para (4), labelled as CAU2, CAU3 and CAU4, respectively. The antiproliferative effect and their underlying mechanism(s) were investigated on both breast (MCF-7R) and ovarian (A2780) cancer cell lines via various in vitro assays. Molecular mechanisms of p53 of both cells upon treatments were analysed via Human p53 signaling pathway RT2 profiler PCR array with all other supportive parameters such as cell proliferation, DNA fragmentation, cell invasion, cell cycle analysis, Anexin V/FITC and caspases (3, 8, 9 and 10). All compounds (CAU2, CAU3 and CAU4) exhibited strong cytotoxicity against MCF-7R and A2780 cell lines with IC50 of 8.14 μM, 7.26 μM and 9.03 μM against the former cell lines and 1.19 μM, 2.28 μM and 0.785 μM against the latter cell lines, respectively. Apoptotic cell death was confirmed by DNA fragmentation and Annexin V assay, respectively. The treated compounds also induced caspases (caspase-3/7, -8, -9, -10) expressions at both cancer cells which led to apoptosis. Both types of cancer cells were arrested at S-phase checkpoint upon treatment with the treated compounds. All treated compounds were shown to induce both intrinsic and extrinsic apoptotic pathways, supported and confirmed by the data obtained from Human p53 signaling pathway RT2 profiler PCR array and caspases activities assay, respectively. The compounds were also able to significantly modulate several important gene expressions such as p53, p73 and Bax via upregulation whilst simultaneously downregulated key anti-apoptotic gene bcl-2. Downregulation of MDM2 gene has also been observed, as it served as the destructive factor for p53 gene. The compounds also inhibited the NF-κB signaling pathway via activation of Lys48-linked polyubiquitination thus led to NF-κB degradation. Furthermore, the accumulation of reactive oxygen species (ROS) was observed upon the compounds’ treatment, indicating the ROS generation thus led to the increment of mitochondrial membrane potential (MMP). Consequently, this led to the increase of cytochrome c releases from mitochondria, manifested by the results obtained by flow cytometric analysis. In conclusion, CAU2, CAU3 and CAU 4 exhibited significant anticancer effects against both breast and ovarian cancer by inducing intrinsic and extrinsic apoptotic cell death, respectively. These findings shed a light for furthering the research in the new discovery of novel chemotherapeutic agents.